2013
DOI: 10.4028/www.scientific.net/amm.275-277.1640
|View full text |Cite
|
Sign up to set email alerts
|

Study on Hypolipidemic Activities of Safflower Seed Oil

Abstract: Safflower seed oil is known to be one of the richest natural sources of linoleic acid (LA), with values of up to 69.5% of the total fatty acids. Linoleic acid is known to has important biological activity and its absence in a normal diet has been described as responsible for the development of a wide variety of diseases. This work reported purified LA from safflower seed oil could lower blood liquids level of rats with hyperlipidemia. It showed that purified LA from safflower seed oil could decrease the serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It has been proved that AI is the risk factor of occurrence and development of atherosclerosis and CVDs. [ 37 ] Therefore, CSO may be used as a natural medicine to prevent and mitigate these diseases.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proved that AI is the risk factor of occurrence and development of atherosclerosis and CVDs. [ 37 ] Therefore, CSO may be used as a natural medicine to prevent and mitigate these diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors in the literature have used safflower oil in rat diets and reported that there were no changes in the weights of the organs (heart, spleen, liver, lung, kidneys, stomach, intestines) that were fed the rations with this oil (TSO et al, 2012;GUO et al, 2013;APPLETON et al, 2015).…”
Section: Discussionmentioning
confidence: 99%